IAS / IFRS standards: Fair value issues - Bouderbala, Sarah Hadda (Dirassat Journal Economic Issue, 2015)
The place of fair value in standardizing and regulating of international organizations has continued to grow in importance in research, and especially after the publication of the IFRS13. This work was interested to examine the advantages and disadvantages of fair value, its use is favored by IASB. In Algeria, this problem is little discussed for lack of financial markets.